Impact of meta platforms on organic and paid ROI in small businesses - Hail, Khaled Majeed Saif (Review of Management, Accounting, and Business Studies, 2025)
The growing reliance on social media platforms has intensified the need for small businesses to justify marketing investments through measurable return on investment (ROI). This study examines the impact of organic and paid marketing strategies on Meta platforms, specifically Facebook and Instagram, with a focus on small business contexts. Using a quantitative, descriptive, and comparative research design, data were collected through structured questionnaires and platform analytics from small business owners and digital marketers. The findings indicate that organic marketing is widely adopted and contributes to sustained engagement and brand presence, though its ROI is often perceived as moderate and long term. Paid marketing, by contrast, is perceived as more effective in generating immediate and measurable outcomes, particularly sales, even with modest advertising budgets. However, limited use of analytics tools suggests that ROI assessments are frequently subjective rather than data-driven. Overall, the results demonstrate that organic and paid marketing strategies play complementary roles on Meta platforms. This study contributes to the literature by providing empirical evidence on how small businesses can balance organic and paid efforts to achieve sustainable ROI and offers practical insights for more effective marketing decision making in resource-constrained environments.